Cooperating with Higher Education Institutions as Part of Innovative Strategizing of Science-Based Companies - Vladimir V. Galaiko; Galina I. Yurkovskaya; Artem V. Kharebin (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Science-based enterprises may cooperate with universities to increase their competitive advantage in the radio-electronic industry. The article describes advantages and disadvantages of this strategy on the market of civil products with patent protection for high-tech radio-electronic enterprises. The academic cooperation may offer a solution to the problem of increasing the percentage of high-tech civilian products in the total volume of a high-tech enterprise. The authors interpreted numerous definitions of the concept of strategy of innovative development to develop one of their own. The new strategy of cooperation between high-tech enterprises and universities presupposes creating an innovative ecosystem at university departments. The resulting definition of the concept of the innovative ecosystem of a university department was compared with those available. By obtaining a new line of civilian products with competitive advantages, science-based enterprises are sure to benefit from the cooperation with universities in the fieldof radio-electronic production.